ASSESSMENT OF RISK FACTORS ASSOCIATED WITH ACUTE RESPIRATORY INFECTIONS (ARIS) AMONG CHILDREN UNDER 5 YEARS OF AGE, PAKISTAN - Adeel, Tanzeela; Widiatmoko, Dono (Universitas Airlangga, 2024)
Introduction: Acute respiratory infections account for approximately 6% of the total global burden of disease; almost double the proportion compared with the other communicable diseases. Aims: To investigate the link between risk factors & ARIs in Pakistani pediatric population under 5 with different socio-demographic profiles. Methods: Research was conducted as a cross-sectional study, utilizing the Pakistan DHS 2017-18 data, after ethical approval for the utilization of the dataset. Study variables were defined as age and gender of the child, place of residence, maternal education, wealth index, breastfeeding, and the immunization status of the child. Sample size (n = 39,799) was determined as per the inclusion and exclusion criteria. Prevalence of ARIs was estimated and the association between ARIs and socio-demographic factor and child’s immunization was examined. Results: Out of 39,799 children, 51.6% were males, 21.0 % were aged 36 – 47 months, 73.7% were the rural residents, 23% belonged to lowest wealth index quintiles. The mothers of 43.7% children were illiterate and 55.7% of the children were breastfed. ARIs proportion among the sample was 14.3%. Significant association was observed between ARIs and age (p=0.000), gender of the child (p=0.001), residence (p=0.000), economic deprivation (p=0.000), maternal education (p=0.000) and breastfeeding (p=0.000), vitamin A administration (p=0.021), BCG (p=0.008), pentavalent (p=0.008), measles (p=0.000), and pneumococcal vaccination (p=0.020). Conclusion: Socio-demographic characteristics, i.e., age and gender of the child, accommodation, economic deprivation, maternal education, breast-feeding and poor vaccination uptake were observed to be positively correlated with ARIs among children under 5 years of age in Pakistan.